The Effect of Virtual Reality on Motor Anticipation and Hand Function in Patients with Subacute Stroke: A Randomized Trial on Movement-Related Potential - Ling Chen; Yi Chen; Wen Bin Fu; Dong Feng Huang; Wai Leung Ambrose Lo (Neural Plasticity)
Background. Impaired cognitive ability to anticipate the required control for an upcoming task in patients with stroke may affect rehabilitation outcome. The cortical excitability of task-related motor anticipation for upper limb movement induced by virtual reality (VR) training remains unclear. Aims. To investigate the effect of VR training on the cortical excitability of motor anticipation when executing upper limb movement in patients with subacute stroke. Methods. A total of thirty-six stroke survivors with upper limb hemiparesis resulting from the first occurrence of stroke within 1 to 3 months were recruited. Participants were randomly allocated to the VR intervention group or conventional therapy group. Event-related potentials (ERPs) and electromyography (EMG) were used to simultaneously record the cortical excitability and muscle activities during palmar grasp motion. Outcome measures of the contingent negative variation (CNV) latency and amplitude, EMG reaction time, Upper Limb Fugl-Meyer Assessment (UL-FMA), Action Research Arm Test (ARAT), and National Institutes of Health Stroke Scale (NIHSS) were recorded pre- and postintervention. The between-group difference was analysed by mixed model ANOVA. Results. The EMG onset time of the paretic hand in the VR group was earlier than that observed in the control group (t=2.174, p=0.039) postintervention. CNV latency reduction postintervention was larger in the VR group than in the control group (t=2.411, p=0.021) during paretic hand movement. The reduction in CNV amplitude in the VR group was larger in the VR group than in the control group (p<0.001 for all electrodes except for C3) when executing paretic hand movement. ARAT and UL-FMA scores were significantly higher in the VR group than in the control group (p=0.019 and p=0.037, respectively) postintervention. No significant difference in the reduction in NIHSS was found between the VR and control groups (p=0.072). Conclusions. VR intervention is superior to conventional therapy to improve the cognitive neural process of motor anticipation and reduce the excessive compensatory activation of the contralesional hemisphere. The improvements observed in the cognitive neural process corroborated with the improvements in hand function.